KAJIAN USER EXPERIENCE TERHADAP ASPEK REALISME DALAM GAME DIGITAL 3D - I Nyoman Natanael; Dewi Isma Aryani (Universitas Trisakti, 2021)
AbstractUser Experience Analysis for Realism Aspect in 3D Digital Game. The reality(realism) that is presented in digital games through a first or third-person perspectiveis usually owned by games with the role-playing type, where the player seems to play a role as a character according to the storyline contained in the game. This will further strengthen the realism aspect that is felt by the player. The realism aspect is one of the aspects that supports the immersive nature of a game, the player will feel very deeply involved in the role of the game being played so that it seems as if they are in the game world. The experience of playing at an immersive level will bring joy to the players so that the realism aspect is one aspect that plays a role in the success of a game. This study examines the player’s experience according to its realism aspect in 3D games and the results can be used in the development process of a game. AbstrakKajian User Experience Terhadap Aspek Realisme dalam Game Digital 3D.Kenyataan (realisme) yang dihadirkan dalam game digital melalui sudut pandang orang pertama atau ketiga biasanya dimiliki oleh game dengan jenis role-play, dengan situasi pemain seolah-olah bermain peran sebagai tokoh atau karakter sesuai dengan alur cerita yang terdapat dalam game tersebut. Hal ini akan semakin memperkuat aspek realisme yang dirasakan oleh pemain. Aspek realisme merupakan salah satu aspekyang menunjang sifat imersif dari suatu game, pemain akan merasa sangat menghayati peran dalam game yang sedang dimainkan sehingga seolah berada dan menyatu di dalam dunia game. Pengalaman bermain pada tingkat imersif akan membawa perasaan senang bagi pemainnya, sehingga aspek realisme merupakan salah satu aspek yang berperan dalam kesuksesan sebuah game. Penelitian ini mengkaji pengalaman pemain menurut aspek realismenya dalam game 3D dan hasilnya dapat dipergunakan dalam tahap proses pengembangan suatu game.